Concentration‐QT modelling in early clinical oncology settings: Simulation evaluation of performance. Issue 3 (9th September 2021) - Cantet, Gael; Berges, Alienor; O'Sullivan, Rhianna; Cohen‐Rabbie, Sarit; Dota, Corina; Dubois, Vincent; Benoist, Guillemette E.; Tomkinson, Helen; Rekić, Dinko; Parkinson, Joanna; Schalkwijk, Stein
Abstract : Aims: Concentration‐QT modelling (C‐QTc) of first‐in‐human data has been rapidly adopted as the primary evaluation of QTc interval prolongation risk. Here, we evaluate the performance of C‐QTc in early oncology settings (i.e., patients, no placebo or supratherapeutic dose, 3 + 3 designs). Methods: C‐QTc performance was evaluated across three oncology scenarios using a simulation‐estimation approach: (scen1) typical dose‐escalation testing six dose levels ( n  = 21); (scen2) small dose‐escalation testing two dose levels ( n  = 9); (scen3) expansion cohorts at one dose level ( n  = 6–140). True ΔΔQTc effects ranged from 3 ms ("no effect") to 20 ms ("large effect"). Performance was assessed based on the upper limit of the ΔQTc two‐sided 90% CI against a threshold of 10 or 20 ms. Results: The performance against the 10 ms threshold was limited based on C‐QTc data from typical dose escalation (scen1) and acceptable performance was observed only for relatively large expansions ( n  ≥ 45; scen3). Performance against the 20 ms threshold was acceptable based on C‐QTc data from a typical dose escalation (scen1) or dose expansion cohort n  > 10 (scen3). In general, pooling C‐QTc data from dose escalation and expansion cohorts substantially improved the performance and reduced the ΔQTc 90% CI width. Conclusion: C‐QTc performance appeared limited using a 10 ms threshold, but acceptable against a 20 ms threshold. Selection of threshold may be informed by the benefit–risk balance in a specific disease area. Acceptable precision (i.e., confidence intervals) of the estimated ΔQTc, regardless of its magnitude, can be facilitated by pooling data from dose escalation and expansion cohorts.